High throughput isolation and glycosylation analysis of IgG-variability and heritability of the IgG glycome in three isolated human populations - Pucić, Maja; Knezević, Ana; Vidic, Jana; Adamczyk, Barbara; Novokmet, Mislav; Polasek, Ozren; Gornik, Olga; Supraha-Goreta, Sandra; Wormald, Mark R; Redzić, Irma; Campbell, Harry; Wright, Alan; et al. (Molecular & cellular proteomics, 2011)
All immunoglobulin G molecules carry N-glycans, which modulate their biological activity. Changes in N-glycosylation of IgG associate with various diseases and affect the activity of therapeutic antibodies and intravenous immunoglobulins. We have developed a novel 96-well protein G monolithic plate and used it to rapidly isolate IgG from plasma of 2298 individuals from three isolated human populations. N-glycans were released by PNGase F, labeled with 2-aminobenzamide and analyzed by hydrophilic interaction chromatography with fluorescence detection. The majority of the structural features of the IgG glycome were consistent with previous studies, but sialylation was somewhat higher than reported previously. Sialylation was particularly prominent in core fucosylated glycans containing two galactose residues and bisecting GlcNAc where median sialylation level was nearly 80%. Very high variability between individuals was observed, approximately three times higher than in the total plasma glycome. For example, neutral IgG glycans without core fucose varied between 1.3 and 19%, a difference that significantly affects the effector functions of natural antibodies, predisposing or protecting individuals from particular diseases. Heritability of IgG glycans was generally between 30 and 50%. The individual's age was associated with a significant decrease in galactose and increase of bisecting GlcNAc, whereas other functional elements of IgG glycosylation did not change much with age. Gender was not an important predictor for any IgG glycan. An important observation is that competition between glycosyltransferases, which occurs in vitro, did not appear to be relevant in vivo, indicating that the final glycan structures are not a simple result of competing enzymatic activities, but a carefully regulated outcome designed to meet the prevailing physiological needs.